Future Solar Energy Devices - Girtan, Mihaela (SpringerBriefs in Applied Sciences and Technology,, 2018)
This book addresses electronics and the rise of photonics, and asks what the future holds in store for this technology. It highlights the latest research on all types of solar cells and photonic devices, and a new approach combining photonics and electronics. Beyond simply explaining the existing systems or providing a synthesis of the current state of knowledge, the book also offers readers new perspectives for their own research. Lastly, drawing on the interconnections between electronics and photonics, the book suggests a possible means of using solar energy directly with the aid of future photonic devices.